Development of bottled green mango juice base - Adversario, Paz Asuncion L.; Alabastro, Estrella F. (1989., 1989)
The study was undertaken to develop a bottled green mango juice base to be utilized into ready-to-drink green mango juice drinks. A preliminary study established a dilution ratio of 1:2 (Base:water, v/v) in the preparation of the juice drink. Green mangoes of the Carabao variety at the third day after harvest was shown to be the most appropriate variety/ripeness level. The second phase of the study showed that filtration did not affect the intensity of the green mango flavor and texture of the juice drink, sensory evaluation showed that the panelists preferred the unfiltered green mango juice base with a moderately thick consistency over the filtered juice base with thin consistency. Finally, the heat treatment of 71°C for 10 seconds applied to the green mango juice base was shown to be adequate through microbiological tests and the green mango juice drink prepared from this base was judged by a panel to have the right strength of green mango flavor.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruit juices; Mango